Urban protests. A counter-hegemonic intervention in the neoliberal city? - Kolb, Petra (Momentum Quarterly, 2025)
This article presents the results of the Hamburg ’Right to the City’ movement, which was analysed applying he hegemony discourse analysis of the Essex School (1991) against a radical democratic background. With the intention of revealing its programmatic structure and determining discursive identity in the political space, whereby a selected text corpus of the movement from the period 2017–2021 was analysed. This made it possible to determine the identity and its arrangement in the political space. Within the discourse, numerous demands are articulated that aim to deepen democratic rights and give citizens the power to act in the form of collective self-organisation. The objective is to convey the questions of how the Hamburg ‘Right to the City’ movement challenges the current order of neoliberal urban planning and constitutes a counter-design to the established hegemonic order through its programmatic profile. Based on the articulation of various radical democratic and urban political demands, alternative models in the field of urban planning are demonstrated. With the goal to establish a just city and to move closer to the right to the city for all.